A Multi-Facet Survey on Memetic Computation - Chen, Xianshun; Ong, Yew-Soon; Lim, Meng-Hiot; Tan, Kay Chen (IEEE transactions on evolutionary computation, 2011)
Memetic computation is a paradigm that uses the notion of meme(s) as units of information encoded in computational representations for the purpose of problem-solving. It covers a plethora of potentially rich meme-inspired computing methodologies, frameworks and operational algorithms including simple hybrids, adaptive hybrids and memetic automaton. In this paper, a comprehensive multi-facet survey of recent research in memetic computation is presented.